Cannabis use and dependence among festival attendees: results from the French OCTOPUS survey - Sarah Chaaban; Marion Istvan; Benoit Schreck; Pauline Laigo; Morgane Rousselet; Marie Grall-Bronnec; Stéphanie Pain; Caroline Victorri-Vigneau (BMC, 2024)
Abstract Background Chronic use of cannabis is associated with an increased risk of psychosocial, mental and physical health impairments. Sociohealth institutions reach a very limited proportion of cannabis users in need of treatment. Using data collected from festival attendees, this study aimed to estimate the prevalence of dependent cannabis users and to characterize cannabis dependence. Methods We used data from the cross-sectional OCTOPUS survey carried out at 13 music events in the French department of Loire-Atlantique between July 2017 and July 2018. 383 participants aged 18 or older underwent a face-to-face interview about their basic sociodemographics, tobacco use, alcohol use and past-year substance use. Using the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV) criteria, we estimated the prevalence of dependent cannabis users and characterized their dependence. Results More than two-thirds of participants reported that they had used cannabis in the past 12 months. Among 194 regular cannabis users (at least monthly), 63.4% were dependent. At least 40% of regular users reported health and/or social consequences of cannabis use. Compared to nondependent cannabis users, dependent cannabis users were more likely to be stimulant users and hallucinogen users. Conclusions Dependent cannabis use is common among festival attendees, especially among stimulant or hallucinogen users. Festival settings may be important arenas for i) implementing efficient harm reduction measures to prevent dependence and ii) providing information on care structures and promoting the use of care to dependent users. In addition, healthcare professionals should be aware of trends in polysubstance use among dependent cannabis users.